Beclin1-mediated ferroptosis activation is associated with isoflurane-induced toxicity in SH-SY5Y neuroblastoma cells - Liu Ruizhu; Li Xuefeng; Zhao Guoqing (Acta Biochimica et Biophysica Sinica)
Abstract The widely used inhalation anesthetic, isoflurane, potentially induces neuronal injury in clinical practice. Previous studies showed multiple forms of cell death that resulted from isoflurane-induced cytotoxicity, but the precise underlying mechanism remains poorly understood. Ferroptosis has recently been identified as a non-apoptotic form of regulated cell death. Here, we found that ferroptosis inhibitors, ferrostatin-1 and deferoxamine mesylate (DFOM), showed great efficiency in maintaining cell viability in SH-SY5Y neuroblastoma cells exposed to a high concentration of isoflurane for 24 h. We also observed that cellular chelatable iron and lipid peroxidation were increased in a concentration-dependent manner in response to isoflurane. In addition, isoflurane upregulated Beclin1 phosphorylation, followed by the formation of a Beclin1-solute carrier family 7 member 11 (SLC7A11) complex, which affected the activity of cystine/glutamate antipoter and further regulated ferroptotic cell death. Accordingly, Beclin1 overexpression aggravated isoflurane-induced cell damage by upregulating ferroptosis. This phenomenon was significantly attenuated by silencing of Beclin1 in SH-SY5Y cells. These findings indicate that Beclin1 may regulate ferroptosis in a manner involving inhibition of glutamate exchange activity of system xc(−), which is implicated in isoflurane-induced toxicity. In particular, when isoflurane is administrated at high concentrations and for an extended duration, ferroptosis is more likely to play a crucial role in isoflurane-induced toxicity.